(untitled) (International Journal of Current Engineering and Technology, 2014)
L. rohita, the common freshwater cyprinid in Pakistan, is currently living in such habitats that are contaminated with heavy metals. Copper and lead metals are considered as the strong aquatic pollutants in this area. The aim of the study was to determine 96h LC50 values of copper sulphate [CuSO4.5H2O] and lead nitrate [Pb(NO3)2] for L. rohita and also to demonstrate the effects of their acute concentrations on hematology and serum biochemistry of the candidate fish. The 96h LC50 values for [CuSO4.5H2O] and [Pb(NO3)2] were found to be 3.15 mg/L and 6.80 mg/L respectively. Based on LC50 values, the experiments were conducted for 96h at acute concentrations of [CuSO4.5H2O] and [Pb(NO3)2] and data revealed a significant decrease (P<0.01) in RBC count, Hb, WBC count, and PCV. In contrast, a significant increase (P<0.01) in mean corpuscular hemoglobin concentration (MCHC) values was observed for treated groups indicating the signs of anemia. Among biochemical indices, the significantly higher values (P<0.01) for plasma NH3, LDH, TRIG, CHOL, LDL, VLDL, UA, CPK, and BRN were observed in experimental groups compared with the control. In contrast, lower value of AP, UR, HDL and ALB were observed in treated groups compared with control. The study revealed that copper sulphate and lead nitrate are toxic agents for L. rohita. The study also apprehends the fish consumers as a diet towards the similar hematological and biochemical consequences with the consumption of such metal accumulated fish meat.